Can food technology innovation change the status of a food security crop? A review of cassava transformation into "Bread" in Africa - Abass, A.; Awoyale, W.; Alenkhe, B.; Ndavi, M.; Asiru, B.; Manyong, Victor; Sanginga, N. (Informa UK Limited, 2018)
Reducing both hunger and high expenditure on food imports is a priority for most developing African countries. Countries that hitherto have relied heavily on food imports are seeking new approaches to increase the utilization of locally grown crops. This review uses the case of cassava to propose that scientific and technological innovations, supported by public investment and appropriate policies, offer opportunities for better utilizing locally grown crops, encouraging agro-industrial development, reducing import expenditure and providing much-needed income (“bread”) to smallholders. The review highlights areas that require further research in order to achieve sustainable development in the processing of raw cassava root into cassava flour for bread production.